Theoretical and Methodological Aspects of the Study of Vernacular Proverbs - Granbom-Herranen, Liisa (Tautosakos darbai, 2026)
A vernacular proverb is a part of common language in everyday use. It is used or referred to if it lends some additional value to a speech situation. In folklore studies, the approach to proverbs comes from how people understand and use them. This article concentrates on proverbs used in Finnish everyday life in the 20th and 21st centuries. Finding relevant research material and interpreting proverbs take centre stage in the study of everyday proverbs in common language within their contexts of use. The main questions raised in this article can be summarised as four points. The first point is to decide the definition of a proverb used in everyday practices and common language. The second point is where to find proverbs in everyday use and vernacular language. Connected to this, the third point is how to identify them in the contexts of use. The fourth point, which may be the most demanding task, is to understand how a proverb has been interpreted and to what ends it has been used in different environments and circumstances. The article presents challenges and issues as well as some methodological theoretical solutions relating to how proverbs are used in everyday life. Such challenges, it may be noted, are encountered in any study of micro-folklore focused on everyday life.